Ways of technical support of decarbonization - Struchaiev, Mykola; Стручаєв, Микола Іванович; Стручаев, Николай Иванович (My University, 2021)
The transition to renewable fuels such as straw, husks, briquettes, pellets only mathematically maintains a zero balance of CO2 emissions. In fact, emissions from the combustion of these "clean" species are much higher than from the combustion of natural gas. To remove pollutants from flue gases, filters of various types are most often used. Each of them has certain advantages and disadvantages.
Keywords: fuels; decarbonization